2008
DOI: 10.1152/ajpregu.00782.2007
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous sodium pump inhibitors and age-associated increases in salt sensitivity of blood pressure in normotensives

Abstract: AY, Lakatta EG. Endogenous sodium pump inhibitors and age-associated increases in salt sensitivity of blood pressure in normotensives. Am J Physiol Regul Integr Comp Physiol 294: R1248-R1254, 2008. First published February 20, 2008 doi:10.1152/ajpregu.00782.2007.-Factors that mediate increases in salt sensitivity of blood pressure with age remain to be clarified. The present study investigated 1) the effects of high-NaCl intake on two Na pump inhibitors, endogenous ouabain (EO) and marinobufagenin (MBG), in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 35 publications
9
62
1
Order By: Relevance
“…Urine MBG excretion (corresponding to each of the 14 24-hour collections) and plasma MBG levels (last week of each sodium condition) were assessed using a competitive fluoroimmunoassay as reported previously in detail (10,(16)(17)(18). Briefly, urine and plasma samples were extracted using C18 SepPak cartridges (Waters Inc., Cambridge, MA), and MBG was measured using a fluoroimmunoassay (Dissociation-Enhanced Lanthanide Fluorescent Immunoassay) based on a murine anti-MBG 4G4 monoclonal antibody recently described in detail (19).…”
Section: Bp and Blood/urine Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine MBG excretion (corresponding to each of the 14 24-hour collections) and plasma MBG levels (last week of each sodium condition) were assessed using a competitive fluoroimmunoassay as reported previously in detail (10,(16)(17)(18). Briefly, urine and plasma samples were extracted using C18 SepPak cartridges (Waters Inc., Cambridge, MA), and MBG was measured using a fluoroimmunoassay (Dissociation-Enhanced Lanthanide Fluorescent Immunoassay) based on a murine anti-MBG 4G4 monoclonal antibody recently described in detail (19).…”
Section: Bp and Blood/urine Assaysmentioning
confidence: 99%
“…Creatinine clearance, MBG clearance, and sodium-filtered and fractional excretion of sodium were calculated as described previously (16). Other blood assays were performed using standard methodology.…”
Section: Bp and Blood/urine Assaysmentioning
confidence: 99%
“…50 This pattern of ouabain response after salt loading has also been observed in Dahl salt-sensitive rats 82,83 and in humans with normal blood pressure. 84 Several lines of evidence support the idea that endogenous ouabain has a prohypertensive role; these include the 'adducin paradigm', 85 the induction of hypertension in ouabain-treated rodents, the elevation of endogenous ouabain levels in hypertensive rats, and the central prohypertensive action of this hormone. In rats, chronic peripheral administration of low doses of ouabain (10-50 μg/kg per day) increased arterial pressure and induced cardiac hypertrophy.…”
Section: Role Of Cardiotonic Steroids In Hypertension Endogenous Ouabainmentioning
confidence: 99%
“…Body reconstructs stress urinary natriuretic function to extrect the sodium retention in the body and increase nocturnal sodium excretion passively, then compensatory elevated blood pressure at night and showed Non-dipper change. (Anderson et al, 2008). It was thought that EO has a more important role in blood pressure regulation, but subsequent research has found the lower concentration of MBG can cause vasoconstriction relative to uabain in blood vessels of individuals.…”
Section: Marinobufagenin and Sodium Excretionmentioning
confidence: 99%
“…Many researches indicated that MBG was closely related to blood pressure (Anderson et al, 2008). It was thought that EO has a more important role in blood pressure regulation, but subsequent research has found the lower concentration of MBG can cause vasoconstriction relative to uabain in blood vessels of individuals.…”
Section: Marinobufagenin and Blood Pressurementioning
confidence: 99%